Criminalization of free speech: Social protest and local administration in Guayaquil - Flores Aguirre, Xavier (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2007)
Through a case study of the detention of thr ee people for protesting in opposition to the M etr o vía, this article analyzes the authoritative natur e of the public politics in G uayaquil. T o do so, the facts are narrated as they wer e seen by the local press, and fitted inside a widespread political practice. F inally , they are contrasted to contemporar y theories of human rights as for freedom of speech. The ar ticle demonstrates the authoritarian and undemocratic character of the local authorities and the need to create spaces that r espect and propitiate the critical debate in r elation with the public politics betw een the authorities and the civil society .